KEPATUHAN PENGOBATAN DAN DUKUNGAN KELUARGA DENGAN RISIKO GAGAL GINJAL KRONIK PADA PASIEN HIPERTENSI - Firmansyah, Anasya; Herlina, Santi (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2024)
Hypertension is a non-communicable condition (NCD) characterized by an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Measuring the success of hypertension treatment is based on the extent to which an individual adheres to treatment. One aspect that plays a role in the level of compliance with hypertension treatment is support from the family. Compliance with hypertension treatment and support from the family is crucial in preventing complications due to high blood pressure. One of the impacts of hypertension is chronic kidney failure. The aim of this study was to examine the correlation between adherence to hypertension treatment and family support and the risk of developing chronic kidney failure. This research is a quantitative study that uses a cross-sectional approach and involves 86 respondents at Depok Regional Hospital who were selected using the purposive sampling method. Data collection used two questionnaires and one observation sheet. Hypertensive patients have a high risk of developing chronic kidney failure. There was no relationship between the risk of chronic kidney failure with gender (p=0.784), education level (p=0.264), duration of suffering from hypertension (p=0.051), adherence to hypertension treatment (0.760), and family support (p=1.000). However, there was a relationship between age (p=0.003) and occupation (p=0.013) with the risk of chronic kidney failure and there was no relationship between adherence to hypertension treatment and family support with the risk of chronic kidney failure.